Social factors influencing diabetes mellitus in adults attending a tertiary care hospital in Nagpur: a cross sectional study - Patil, Sneha D.; Deshmukh, Jyotsna S.; Patil, Chaitanya R. (International Journal of Research in Medical Sciences, 2017)
Background: Social determinants of the health are the conditions in which individuals are born, grow, live and age. Increasingly, these are being recognized for their relationship to the soaring incidence of diabetes mellitus. So, we conducted a study to find the social factors of diabetes mellitus. Methods: A cross sectional study was conducted in adults having type 2 diabetes in outpatient department of tertiary care institute in Nagpur from July to September 2015. Socio demographic factors, health care access factors, stress related factors and self-care behavior of these patients were studied. Data was analyzed using Epi Info 7.1 software. Results: Out of 140 diabetic patients studied females were predominant (55.71%). Most of them were married (92.85%), were Muslim by religion (47.14%), were from nuclear families, (53.57%) and lower middle class (40%). 50% said that they have health care facilities nearby their house and 50.71% do not get drugs regularly in that health care facility. and only (27.14%) were insured. 64.28% of study subjects said that they were accompanied by relatives to hospital. The financial stress (73.57%) and family stress (72.85%) was more in the patients than work stress (49.28 %). 75.72% and 71.42 % checked their blood sugar levels every 6 monthly and blood pressure every monthly and very less patients kept follow up for complications. Conclusions: Our study showed that in spite of having health care facility nearby, the irregularity of drugs was a major concern. Very less study subjects were insured for their health, this implicates higher stress related factors. They had less compliance towards follow-up of complications of diabetes mellitus.